Pengembangan Modul Elektronik Fisika Berbasis Web dengan Pendekatan Computational Thinking pada Materi Momentum dan Impuls Kelas X SMA - Rahmawati, Atina; Fauzi, Ahmad; Ekawati, Elvin Yusliana (Jurnal Materi dan Pembelajaran Fisika, 2022)
This study aims to: explain the development procedure, feasibility, and characteristics of a web-based electronic module with a computational thinking approach on momentum and impulse material for class X SMA. The research method used is RnD (Research and Development) with a modified Borg and Gall development model until the seventh stage, namely the revision of the main product. Sources of research data were obtained from two experts, three reviewers, three peer reviewers, and 84 students. Qualitative data were taken through interviews and open questionnaires and then analyzed using the Miles and Huberman model. Quantitative data was taken through a closed questionnaire and then analyzed by descriptive analysis. Conclusions from this study: (1) the module development procedure was carried out with research and information gathering, planning, initial product development, initial field trials, initial product revisions, main field trials, and main field trial product revisions; (2) the feasibility of expert validation, reviewer and peer reviewer assessment, and field trials show that the developed electronic module meets the criteria very well; (3) the characteristics of the electronic module developed are using computational thinking learning flow which is equipped with picture and video illustrations, reflections, virtual labs, and practice questions with automatic feedback.